Restricted Diffusion in Bilateral Optic Nerves and Retinas as an Indicator of Venous Ischemia Caused by Cavernous Sinus Thrombophlebitis - Chen, J.S.; Mukherjee, P.; Dillon, W.P.; Wintermark, M. (American Journal of Neuroradiology, 2006)
SUMMARY: A 44-year-old man developed bilateral blindness following severe periorbital cellulitis and pansinusitis. CT and MR imaging demonstrated bilateral cavernous sinus thrombosis. Diffusion-weighted imaging revealed reduced apparent diffusion coefficient in bilateral optic nerves, suggesting optic nerve ischemia caused by the cavernous sinus thrombophlebitis (CST). Following surgical debridement of pansinusitis, antimicrobial therapy, and anticoagulation, the patient recovered from the infectious episode but sustained permanent bilateral blindness. This case shows that both retinal and optic nerve ischemia can be the cause of blindness after CST. Arguments supporting an arterial-versus-venous origin for the ischemia are discussed.